A Method for Calculating of the Efficiency of Communication Systems with Multiple Modulation Types and Multi-Stage Composite Coding - E. B. Lipkovich; V. V. Rabtsevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Analytical relations and a methodology for calculating the performance indicators of communication and multimedia broadcasting systems using multi-position modulation types (QAM-M, FM-M, FM-M, CHMS-M, AM-M, OFM-M) and multi-stage coding based on non-systematic convolutional codes and non-binary block Reed-Solomon codes are proposed. The relations obtained are common for studies of noise immunity, corrective capacity, energy and information efficiency of systems, depending on the requirements for reception reliability, modulation format, type of codes used and their parameters. The calculation of the characteristics of systems with cascade composite coding is carried out in a closed form and does not require the use of complex computer simulation procedures.